The Influence of Product Quality, Price Fairness, Brand Image, and Customer Value on Purchase Decision of Toyota Agya Consumers: A Study of Low Cost Green Car - Simbolon, Freddy Pandapotan; Handayani, Elvira Rossi; Nugraedy, Menik (Binus Business Review, 2020)
The research aimed to investigate the influence of product quality, price fairness, brand image, and customer value on purchase decision in the Low Cost Green Car (LCGC). The research applied a quantitative method with survey design. It was conducted in Auto2000 Jakarta with a sample of 100 Toyota Agya owners using an accidental sampling technique. Data analysis for hypothesis test used path analysis calculated with SPSS software. The research findings indicate that product quality, brand image, and customer value significantly influence the purchase decision of Toyota Agya consumers. Meanwhile, price fairness has no effect on the purchase decision. The results also show that product quality, price fairness, and brand image affect customer value. Based on these findings, in developing LCGC, manufacturers must pay attention to product quality, build brand reputation, and create more value for consumers.